Diversidade endoparasitária em peixes de riachos da bacia do rio Pirapó, Estado do Paraná, Brasil : uma abordagem ecológica. - Moreira, Luis Henrique de Aquino (2013)
An ichthyoparasitological study was conducted with 166 fishes, belonging to the species Poecilia reticulata, Rhamdia quelen and Hypostomus ancistroides in tributaries streams of Pirapó river. These streams are located in urban and rural area around the city of Maringá-PR. The urbanized streams traverse the urban area of the city, have compromised their riparian (deforested), the surrounding edifications, receiving effluents from sewage treatment plant (ETE) and illegal connections. On the other hand, rural streams had the opposite characteristics commented out in urban streams. The research aimed to survey on endoparasites of fishes analyzed, as well as improve the knowledgement about the host / parasite relationship on site. Thus, we analyzed the correlation between the total length of the fish with levels of parasitism (prevalence, abundance). Due to the existence of sexual dimorphism in the species Poecilia reticulata, were investigated possible influences of sex this fish in parasitism. We also assessed the possibility of using fish endoparasites to determine the environmental quality of streams. Only 15.06% of endoparasite prevalence was observed in the hosts investigated. A pentastomid species, Sebekia oxycephala (Diesing) Sambon, 1922 and cestode belonging to the order Pseudophyllidea were endoparasites found parasitizing fish P. reticulata, with a prevalence of 13.89 and 0.92% respectively. R. quelen showed prevalence of 39.13% to nematode species C. (C.) pinnai Travassos, Artigas and Pereira, 1928. . No parasites found in the species H. ancistroides. There was no correlation between the sex of P. reticulata with the prevalence and abundance of S. oxycephala. The hosts? lengths had not correlated with the prevalence and abundance of endoparasites. Jaccard Similarity Index pointed a high similarity between parasites species considering both sets of environments. No influence of streams groups (urban and rural) on the parasites prevalence and abundance was found, even no difference in the distribution of parasites abundances between different streams analyzed. The Relative Condition Factor (Kn) was not different in urban and rural streams to P. reticulata species, but in R. quelen was statistically higher in urban environments. The Kn was independent of parasitism, but was statistically significant in females of P. reticulata when evaluated separately by environment (urban and rural). In urban environments, where are verified changes in water quality, and greater stress occurs in the host, the parasite S. oxycephala becomes more pathogenic resulting in smaller Kn in P. reticulata females. The abundance of the referred parasite species on the P. reticulata females resulted in a negative Kn correlation in urban streams, suggesting parasite potential damaged action in the anthropized streams.Due to parasites found were generalists, there was not observed binding between parasitism with features/peculiarities of analyzed hosts (fishes), as occurs with high specificity parasites. It was verified that the parasite species S. oxycephala and C. (Cucullanus) pinnai are inadequate as bioindicators of environmental quality.